Types of Cyberbullying What Happens Between Middle School Students on Social Media Whatsapp - Faida Nasiroturrohmah; Rustono Rustono; Bernadus Wahyudi Joko Santoso (Universitas Negeri Semarang, 2024)
The choice of words/diction in communication is crucial so there is no discomfort for the person you speak to. In the current era of technological progress, communication is commonly carried out via digital media, especially by the younger generation such as school children. Ignorance of the principles of politeness and the occurrence of a pandemic has had a negative impact on the behavior of the younger generation in communicating. Cyberbullying is an action bullying using digital technology. This research aims to describe the types of cyberbullying carried out by students at the junior high school level in Banyumas Regency. This research is qualitative research using a forensic linguistic approach. The theory of types cyberbullying the theory used is Nancy E. Willard's theory. Research data comes from fragments of group conversations Whatsapp which allegedly contains speech cyberbullying. The research results showed the occurrence of seven types of cyberbullying of eight types of cyberbullying. Apart from that, there are dangers and negative impacts of cyberbullying.